Reasoning and Argument - Schneider, John L. (New York Holt, Rinehart and Winston, Inc., 1967)
In many situations, you, as a responsible citizen, must think and decide. That is what this book is about-how to reason (think) and how to argue (decide). You will find much here to discuss with your classmates.
Keywords: Writing